2021
DOI: 10.1016/j.jsv.2020.115817
|View full text |Cite
|
Sign up to set email alerts
|

Vibration responses of rotor systems in diesel multiple units under dynamic spatial misalignments and base motions

Abstract: To achieve high performance monitoring of the electric transmission powerpack for a Diesel Multiple Unit (DMU), the dynamic responses of the rotor system inside the powerpack with Dynamic Spatial Misalignment (DSM) and base motions from car body are investigated through structural modeling and numerical analysis. A three-dimensional coupled model, including public framework, diesel engine, electric generator and rotor system, is developed. Vibrations under deterministic and random base motions are numerically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The results indicate that the cage fracture leads to the increase in the amplitude of the system. Wu et al [19] researched the random base motions of the rotor system with a misalignment fault in DMU, and the research shows that the nonlinear response of the DSM to the deterministic base motion is faster than the vibration of the rotor. Tuckmantel et al [20] researched the vibration signal of the multi-span rotor structure with clutch under angle misalignment.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that the cage fracture leads to the increase in the amplitude of the system. Wu et al [19] researched the random base motions of the rotor system with a misalignment fault in DMU, and the research shows that the nonlinear response of the DSM to the deterministic base motion is faster than the vibration of the rotor. Tuckmantel et al [20] researched the vibration signal of the multi-span rotor structure with clutch under angle misalignment.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [10] investigated the heat transfer characteristics of a misalignment under purge flow at second stage vane endwall through heat/mass transfer experiments using the naphthalene sublimation method and CFD simulations. Wu et al [11,12] investigated the dynamic responses of dynamic spatially misaligned rotors inside a diesel engine multiple unit system. Aggarwal et al [13] described the incremental inductance method to detect static misalignment of machines.…”
Section: Introductionmentioning
confidence: 99%
“…Establishment of dynamic system equations is the basis for studying the vibration characteristics. Wu et al [10] used the Newmark method to numerically calculate the vibration of the car under basic motion, and the result showed that the system has a good vibration response. ere are many modeling methods for the rotor system.…”
Section: Introductionmentioning
confidence: 99%